The basic of self-management in Asian Folklore - Zainal Abidin, Noraini; Nik Muhamad Affendi, Nik Rafidah (Human Resource Management Academic Research Society, 2021)
Without management, human lives will face with a lot of risk. For example, self-management has become a basic thing that has been exposed since childhood by adults as well as individuals nearby. Such exposure is also applied in children’s books from an early age as a useful initial input. In this case, the management aspect is knowledge-based that has been widely introduced in Asia for a long time. This can be seen in the Koleksi Cerita Rakyat Asia Untuk Kanak-kanak (Buku 1) which has been published by the Dewan Bahasa dan Pustaka as a result of the Asian Copublication Programme, organized by the Asian Cultural Centre for Unesco / Tokyo Book Development Centre, in collaboration with Unesco and the countries of UNESCO members in Asia. The findings also showed that the dominant basis of selfmanagement which covers basic things such as time management, emotions, conflict and hygiene.